Bad Santa - Cameron, John.; Aubrey, Sarah; Weinstein, Bob, 1953-; Ficarra, Glenn; Regua, John.; Zwigoff, Terry; Thornton, Billy Bob.; Cox, Tony, 1958-; Graham, Lauren, 1967-; Kelly, Brett; Tom, Lauren; Ritter, John, 1948-2003.; et al. ([United States] : Dimension Home Video ; Burbank, Calif. ; Distributed by Buena Vista Home Entertainment, 2004)
Willie is a thief who teams up with his dwarf friend Marcus, for a very special Christmas scam. Willie gets a job as Santa Claus at a shopping mall, Marcus tags along as an elf, and they use their employee status to rob stores blind just before Christmas. But Willie is a bitter and foul-mouthed alcoholic who doesn't care much for kids. A mall's manager is certain something's wrong, so he asks the chief of security to check out Willie. Meanwhile, one of the kids Willie is forced to talk to becomes a regular customer.
Special Features Include over 7 minutes of never-before- seen footage: Deleted and alternate scenes, behind-the- scenes special, outtakes, "Badder Santa" gag reel. Specifications: Dolby Digital 5.1 surround sound, widescreen, enhanced for 16x9 televisions.
Special features: director's commentary; behind-the-scenes feature; deleted scenes; tribute to John Ritter.
Director of photography, Jamie Anderson ; editor, Robert Hoffman ; music composer, David Kitay ; costume designer, Wendy Chuck ; production designer, Sharon Seymour.
Billy Bob Thornton, Tony Cox, Lauren Graham, Brett Kelly, Lauren Tom, John Ritter, Bernie Mac.
MPAA rating: R; for pervasive language, strong sexual content and some violence.
Unrated edition. Has pervasive language, strong sexual content and some violence.
Keywords: Department store Santas -- Drama; Shopping malls -- Drama; Robbery -- Drama; Feature films; Comedy films; Video recordings for the hearing impaired